Genetic testing for amyotrophic lateral sclerosis in Canada – an assessment of current practices. Issue 3 (3rd April 2022) - Salmon, Kristiana; Anoja, Nancy; Breiner, Ari; Chum, Marvin; Dionne, Annie; Dupré, Nicolas; Fiander, Amanda; Fok, Daniel; Ghavanini, Amer; Gosselin, Sylvie; Izenberg, Aaron; Johnston, Wendy; et al.
Abstract: Objective: To understand current genetic testing practices at Canadian ALS clinics. Methods: An online survey and phone interviews, with clinicians practicing in 27 ALS clinics in Canada, were employed to collect data. Quantitative and qualitative analyses were conducted. Results: Ninety-three percent (25/27) of ALS clinics in Canada are routinely ordering genetic testing for familial ALS, while 33% (9/27) of clinics are routinely ordering genetic testing for sporadic ALS. Barriers to genetic testing include a perceived lack of an impact on treatment plan, difficulty in obtaining approvals, primarily from provincial Ministries of Health, and limited access to genetic counseling. Predictive testing practices were found to be the most variable across the country. The average wait time for a symptomatic patient living with ALS to see a genetic counselor in Canada is 10 months (range 0–36 months). Conclusions: Access to genetic testing, and testing practices, vary greatly across Canadian ALS clinics. There may be patients with a monogenetic etiology to their ALS who are not being identified given that genetic testing for patients diagnosed with ALS is not routinely performed at all clinics. This study highlights potential inequities for patients with ALS that can arise from variability in health care delivery across jurisdictions, in a federally-funded, but provincially-regulated, health care system. Clinical trials for both symptomatic ALS patients and pre-symptomatic ALS gene carriers are ongoing, and ALS clinicians in Canada are motivated to improve access to genetic testing for ALS.